Design of mechanisms for reversible macroscopic surface patterns - Kalairaj, Manivannan Sivaperuman (2017)
Almost all the electronics and mechanical equipment have controllers to control the entire equipment or some specific component in the equipment to do a certain task. These controllers respond to various types of inputs and performs the function accordingly. One type of input given to the controller is the touch and these controllers which use human touch has touch screen to act as the medium. The touch screen will not give haptic feedback to the users whereas the buttons will take up more unwanted space and also cause disturbance and confusion in recognizing the functions due to ambiguity and also in determining which is active and which is not and also which is required in which situation. In this dissertation we propose buttons on demand with simple sliding mechanism for rapid switching between different button patterns, in which the buttons remain flat in the surface when inactive and protrude out of the surface and appear as button for operation when active. The sliding mechanism will be actuated by means of manual sliding or manual pinion gear adjustment or shape memory actuation. The design and the working of the controller will be explained in this thesis and the application will be more inclined towards automobiles where human-machine interaction plays a major role. The design and simulation are carried out on SolidWorks and the prototypes are fabricated and tested.